Human Violence and Eating Animals: Reading Gaétan Soucy through the lenses of Animal and Vegan Studies - Powers, Scott (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2021)
This essay examines vegetarianism and the treatment of animals in Gaétan Soucy’s L’Immaculée Conception and Music-Hall! as part of an innovative commentary on violence among humans. The novels’ unconventional use of zoomorphism and anthropomorphism in establishing animal sentience and agency places the animal at the center of moral inquiry in order to denounce violent anthropocentrism. By drawing from leading theorists of animal and vegan studies, this essay demonstrates that in Soucy’s works, animals and minority human groups are depicted as sharing a common aggressor: patriarchy and its numerous avatars. By highlighting a number of parallels in the narratives between animals and human victims of male aggression, this study brings to light the novels’ denunciation of the meat processing industry and the consumption of meat as perpetuating a divisive social order that victimizes not only animals, but also women, children, and the poor. In contrast, the narratives proffer respect for animals as the ultimate anti-violent gesture. By extension, vegetarianism presents as a critical, self-reflexive consciousness and a deep ethical awareness that breaks with patterns of violent behavior at the foundation of Western civilization.